Analisis Dampak Proyek Pembangunan Rehabilitasi Jalan Jurusan Mahakam, Kabupaten Lumajang – Batas - Aldillah Fauzi (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2023)
Development is a planned action of change and growth. Siagian (2005: 9) argues that development is "a growth and change effort that is consciously planned and carried out by a nation, state and government towards modernity in the framework of nation building". The aim of the development is to optimize the peace of mind of residents. Development itself is a marker of transformation for a country. As we know, the goal of the Indonesian nation's national development is to achieve a balanced, capable and prosperous society.